Songs as a Medium for Reflecting Cross-Cultural Tensions: An Analysis of the Lyrics of the Song 'Mangu' in the Context of Indonesian Diversity: Penelitian - Putra Darma, Virga; Bernadeta, Anggis; Robbani, Nadzira (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the song Mangu by Fourtwnty as a symbolic medium that reflects the tension in interfaith and cultural relations in Indonesia. Using a qualitative approach and narrative method, this study examines the relationship between song lyrics and the personal experience of an informant named Marhamah Khoirunnisa, who is in a relationship with a couple of different faiths and cultures. The findings show that Mangu's song is not only an expression of personal grief, but also contains a collective narrative of love that is hindered by religious boundaries, family pressure, and established social norms. Lyrics like